Gender i žanr: Mužskoj i ženskij varianty russkogo rečevogo žanra "razgovor po dyšam" - Dementʹev, Vadim V. (Stylistyka, 2004)
Gender causation of the genre framework of speech is explained in this article. Male and female versions of Russian speech genre “razgovor po dusham” (“soul talk”), that vary in the genre topic, style and composition, are researched here. This genre is highly relevant to the system of the basic values of Russian culture.